Efficiency limit for diffusion silicon solar cells at concentrated illumination - Gorban, A.P.; Kostylyov, V.P.; Sachenko, A.V.; Serba, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
A general approach has been developed to calculation of photoconversion efficiency of thinbase silicon solar cells with double-sided metallization for concentrated solar illumination. The full absorption of photoactive radiation has been theoretically simulated, the light absorption by free charge carriers in heavily doped regions in AM0 conditions was taken into account. It was found that the efficiency of photoconversion η at K ≈ 100 can be as high as 27%.